Analisis Tindak Tutur Driver Ojek Online dalam Interaksi dengan Pelanggan: Kajian Bahasa pada Masyarakat Kelas Pekerja Digital - Delima br Pakpahan; Enjel Mitra Wati; Putri Indahyani Tarigan; Yuliana Santa Lore Purba; Berlianta Saragih; M. Oky Fardian Gafari (Universitas Serambi Mekkah, 2026)
This study aims to analyze the speech acts used by online motorcycle taxi drivers in their interactions with customers within the digital working-class community. This research employed a qualitative method with a descriptive approach. The data were collected through direct interviews with six online motorcycle taxi drivers consisting of two Grab drivers, two Gojek drivers, and two Maxride drivers around the environment of Universitas Negeri Medan. Data collection techniques included interviews. The results showed that three forms of speech acts were found in the interaction between drivers and customers, namely locutionary acts, illocutionary acts, and perlocutionary acts. Locutionary acts were used by drivers to convey information related to trips and road conditions. Illocutionary acts were used to maintain customer comfort and build social interaction during the trip. Meanwhile, perlocutionary acts were reflected in the influence of drivers’ speech on customer comfort and application ratings. The study also found differences in communication patterns among Grab, Gojek, and Maxride drivers. However, all drivers emphasized the importance of polite language in providing services to customers. Therefore, language plays an important role in online transportation services and becomes part of the work quality within the digital working-class community.